Inside the head of a cybertype – three-dimensional reconstruction of the head muscles of Ommatoiulus avatar (Diplopoda: Juliformia: Julidae) reveals insights into the feeding movements of Juliformia. Issue 4 (28th November 2019) - Naumann, Benjamin; Reip, Hans S; Akkari, Nesrine; Neubert, David; Hammel, Jörg U
Abstract: The origin and diversification of the arthropod head is one of the major topics in the field of evolutionary morphology of Arthropoda. Among the major arthropod groups, Myriapoda and, more precisely Diplopoda, are generally poorly studied regarding their head anatomy. However, this group is of pivotal importance to understand the evolutionary functional morphology of the arthropod head. In this study, we investigate the complete musculoskeletal system of the diplopod head with a detailed description of the cephalic anatomy of the recently described species Ommatoiulus avatar . The comparison of our data with the literature on the few other species available show that the morphology of the musculoskeletal system within Juliformia, a subgroup of the Diplopoda, is relatively conservative. Using video recordings of the feeding movements in addition to the anatomical data, we revise the mechanism of the mandibular movements in Juliformia. There was a controversy whether mandibular abduction is an active process, facilitated by contraction of an abductor muscle, or if it is a passive process, mediated by tentorial and gnathochilarial movements not involving a direct abduction by muscular contraction. We show that mandibular abduction in Ommatoiulus is an active movement involving the contraction of an abductor muscle. This is similar to the mandibular abduction in other arthropod groups.